Enhancing Reading Comprehension of The Tenth Grade Students of SMA Negeri 1 Torue Through Preview, Question, Read, Summarize, and Test (PQRST Method) - Dewi, Ni Putu Indah Tiara; Hastini, Hastini; Mukrim, Mukrim; Marhum, Mochtar; Left, Left (Universitas Pahlawan Tuanku Tambusai, 2025)
Reading skills are very important for students such as students can get information from reading, students can improve their knowledge, students can expand their way of thinking by reading any text. Thus, this research aims to determine whether using the effectiveness of the Preview, Question, Read, Summarize, and Test (PQRST) method in enhancing reading comprehension skills of tenth-grade students at SMA Negeri 1 Torue. The researcher used purposive sampling approaches to get the sample. Using a quasi-experimental design with 72 participants divided equally into experimental and control group. Data were collected through pre-test and post-test on recount texts. The pre-test measured students' prior knowledge, where as the post-test measured students' improvement in reading comprehension using the PQRST method following the treatment. The results show that the experimental group improves significantly in reading comprehension, with the mean score rising from 59.64 in the pre-test to 87.28 in the post-test. In comparison, the control group showed a modest increase, with mean scores increasing from 65.19 to 75.83. Statistical analyses confirmed the PQRST method that the improvement in the experimental group was statistically significant (p 0.05). The findings show that using the PQRST method successfully improves students' conceptual comprehension and promotes more fair learning outcomes. As a result, it is recommended that the PQRST method be used more widely to teach reading comprehension in senior high schools.